Penerapan Model Inkuiri Sosial dalam Meningkatkan Sikap Ekoliterasi pada Pembelajaran IPS - Megawati, Megawati (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The focus used as the best practice is the social inquiry model to improve eco-literacy attitudes in the environment surrounding social studies learning material with environmental sub-themes for fourth-grade students at SD Negeri 03 Sorek One for the 2023/2024 academic year. The goal to be achieved is through a social inquiry model to improve students' eco-literacy skills and to increase the quality of awareness from an early age to reduce waste so that when they grow up they can change their mindset that waste must be minimized and no longer use the collect-transport-dispose paradigm. and burn. The method used in this research is a qualitative method with an experimental type. The result is that students' eco-literacy attitudes have increased to a very good predicate. This indicates that the eco-literacy program implemented in schools has had a positive impact on students' understanding and awareness of the environment. With this improvement, it is hoped that students will be more concerned and responsible for the surrounding environment and be able to play an active role in preserving nature. It is also hoped that awareness of the importance of the environment will have a positive impact on the sustainability of ecosystems and life on Earth. It is hoped that the results of this research will provide valuable insight for educators in designing more effective learning strategies to prepare a generation that cares about the environment.